2017
DOI: 10.1021/acs.biochem.6b00098
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nucleotide Specificity of Succinyl-CoA Synthetase in Blastocystis: The Emerging Role of Gatekeeper Residues

Abstract: Charged, solvent-exposed residues at the entrance to the substrate binding site (gatekeeper residues) produce electrostatic dipole interactions with approaching substrates, and control their access by a novel mechanism called “electrostatic gatekeeper effect”. This proof-of-concept study demonstrates that the nucleotide specificity can be engineered by altering the electrostatic properties of the gatekeeper residues outside the binding site. Using Blastocystis succinyl-CoA synthetase (SCS, EC 6.2.1.5), we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…In contrast, the presence of GTP or GDP did not stabilize the protein, giving no indication that either nucleotide bound to the K46E/K114D double mutant. The results obtained from both the crystal structures and DSF differ from the results of the kinetic assays, which showed that GTP served as a substrate (Vashisht et al, 2017). One possible explanation is that the different results were owing to the different proteins used.…”
Section: Interactions Of the Ribose And Phosphates Of Adp With Bhscscontrasting
confidence: 56%
See 3 more Smart Citations
“…In contrast, the presence of GTP or GDP did not stabilize the protein, giving no indication that either nucleotide bound to the K46E/K114D double mutant. The results obtained from both the crystal structures and DSF differ from the results of the kinetic assays, which showed that GTP served as a substrate (Vashisht et al, 2017). One possible explanation is that the different results were owing to the different proteins used.…”
Section: Interactions Of the Ribose And Phosphates Of Adp With Bhscscontrasting
confidence: 56%
“…There are no significant structural differences between wild-type Abd-BhSCS and the K46E, K114D and V113L mutants, but the L227F mutant differs in that no magnesium is bound. This change in the structure could account for the higher apparent K m for ATP of the V113L/L227F double mutant (265 AE 50 mM versus 145 AE 47 mM; Vashisht et al, 2017). Kinetic assays for the K46E/ K114D double mutant showed that it can use either GTP or ATP but prefers GTP (143 AE 17 mM versus 230 AE 34 mM; Vashisht et al, 2017).…”
Section: Interactions Of the Ribose And Phosphates Of Adp With Bhscsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Hamblin et al proposed an electrostatic gatekeeper effect, in which the nucleotide access was controlled by the charged amino acids (gatekeeper residues) outside the binding site of the succinyl-CoA synthetase (SCS) of Blastocystis-a human intestinal parasite [6]. Recently, we have experimentally demonstrated the 'electrostatic gatekeeper effect', where the gatekeeper residues were found to be critical for nucleotide specificity in Blastocystis SCS [7]. Interestingly, this study also established a novel enzyme engineering approach, where the switching of the charge of the gatekeeper residues from positive to negative, demonstrated that the ADP-forming SCS could also utilize GTP.…”
Section: Introductionmentioning
confidence: 99%